The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/ijms18122569
|View full text |Cite
|
Sign up to set email alerts
|

A New Bone Substitute Developed from 3D-Prints of Polylactide (PLA) Loaded with Collagen I: An In Vitro Study

Abstract: Although a lot of research has been performed, large segmental bone defects caused by trauma, infection, bone tumors or revision surgeries still represent big challenges for trauma surgeons. New and innovative bone substitutes are needed. Three-dimensional (3D) printing is a novel procedure to create 3D porous scaffolds that can be used for bone tissue engineering. In the present study, solid discs as well as porous cage-like 3D prints made of polylactide (PLA) are coated or filled with collagen, respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 58 publications
1
41
0
2
Order By: Relevance
“…3D scaffolds with a porosity structure is suitable for loading ions, nanoparticles, and biomolecules to achieve multifunctional application. 130 In Correia et al study, 131 the tricalcium phosphate (TCP)/sodium alginate (SA) scaffolds were produced by 3DP. Subsequently, AgNPs were incorporated into scaffolds through two different methods, direct incorporation and physical adsorption.…”
Section: Plasma Electrolytic Oxidation (Peo)mentioning
confidence: 99%
“…3D scaffolds with a porosity structure is suitable for loading ions, nanoparticles, and biomolecules to achieve multifunctional application. 130 In Correia et al study, 131 the tricalcium phosphate (TCP)/sodium alginate (SA) scaffolds were produced by 3DP. Subsequently, AgNPs were incorporated into scaffolds through two different methods, direct incorporation and physical adsorption.…”
Section: Plasma Electrolytic Oxidation (Peo)mentioning
confidence: 99%
“…3D printing is a novel procedure to create 3D porous scaffolds used for bone tissue engineering (Roseti et al ). Solid discs as well as porous cage‐like 3D structures made of PLA coated or filled with collagen were tested for biocompatibility and endotoxin production, respectively (Ritz et al ). This study confirmed the PLA biocompatibility as well as the endotoxin contaminations levels that were below the FDA limit.…”
Section: Pla Biomedical Applicationsmentioning
confidence: 99%
“…Cells can be incorporated as demonstrated by Lee et al, who used collagen as bioink supplemented with pre-osteoblasts [20]. Among others, we printed PLA and collagen to induce tissue regeneration in bone defects [21]. Martin et al printed PLA and functionalized the scaffolds with collagen, minocycline and citrate hydroxyapatite nanoparticles [22].…”
Section: Introductionmentioning
confidence: 99%